RACTA II 2021 : Ricerche di Archeologia Cristiana, Tarda antichità e Alto medioevo : il colloquio internazionale tra dottorandi e dottori di ricerca Roma, 1-3 febbraio 2021 - Benoci, Domenico,; Lombardo, Dino,; Tagliatesta, Federica, (Access archaeology., 2023)
RACTA aims to provide a comprehensive overview of studies on Late Antique and Christian Archaeology, Art History, History, and Early Christian Literature being carried out by young scholars from all over the world. The variety of topics addressed by the 23 authors demonstrates an interdisciplinary methodological approach.